Crack initiation angles and propagation paths in polyurethane foams under mixed modes I/II and I/III loading. (June 2019) - Aliha, M.R.M.; Mousavi, S.S.; Bahmani, A.; Linul, E.; Marsavina, L.
Highlights: Crack initiation behavior of different PUR foams was studied under mixed mode I/II and mixed mode I/III. The path of mixed mode fracture under in-plane and out-of-plane was investigated experimentally using three test specimens. The effect of specimen type, mode mixity and foam density was studied on fracture initiation angle and fracture trajectory. Fracture initiation angle of tested I/II and I/III foam specimens was predicted using the MTS criterion. Abstract: Rigid polyurethane (PUR) foams can be subjected to complex loading conditions when they are utilized as a structural material in engineering components. Under the influence of tensile or shear loads, the crack growth is one of the major failure modes for such cellular materials. Understanding the critical load carrying capacity and also the direction or path of crack growth in PUR foams is of practical interest for designers of foam made structures. The focus of this paper is to study the fracture initiation angle ( θ 0 ) and the trajectory of fracture path for rigid PUR foam materials subjected to in-plane mixed mode I/II and out-of-plane mixed mode I/III fracture deformations. A number of mixed mode I/II fracture experiments using asymmetric-semi-circular bend (ASCB) and compact tension-shear (CTS) specimens and also mixed mode I/III fracture tests using the edge notch disc bend (ENDB) specimen were conducted on closed-cell foam with different densities. The corresponding values of critical fracture resistance ( K Ic, K IIc, or K IIIc ), fracture initiation direction and fracture growth trajectory was obtained for the tested specimens made of PUR foam. The results showed the significant influence of specimen type and mode mixity on both fracture resistance value and fracture initiation direction. While the crack growth trajectory of mixed mode I/II (i.e. tensile/in-plane shear) was along the plane of initial crack but the mixed mode I/III (i.e. tensile/out-of-plane tear) trajectory of ENDB specimens was twisted from the crack front. For all tested specimen the trajectory of fracture for symmetric loading condition was self-similar and along the direction of initial crack plane. However, by adding the contribution of in and out of plane sliding to the crack growth mechanism of tested specimens, the fracture trajectory was kinked from the crack front and extended along a curvilinear path relative to the crack plane. The most deviation in the fracture trajectories were observed under pure modes II and III loading conditions. Despite the fracture toughness value that was significantly dependent on the foam density the direction of fracture initiation angle and the path of fracture growth was not affect noticeably by the density of foam. The mixed mode fracture initiation angles were also in good agreement with the prediction of maximum tangential stress theory.